The trauma film paradigm as an experimental psychopathology model of psychological trauma: intrusive memories and beyond. (July 2016) - James, Ella L.; Lau-Zhu, Alex; Clark, Ian A.; Visser, Renée M.; Hagenaars, Muriel A.; Holmes, Emily A.
Abstract: A better understanding of psychological trauma is fundamental to clinical psychology. Following traumatic event(s), a clinically significant number of people develop symptoms, including those of Acute Stress Disorder and/or Post Traumatic Stress Disorder. The trauma film paradigm offers an experimental psychopathology model to study both exposure and reactions to psychological trauma, including the hallmark symptom of intrusive memories. We reviewed 74 articles that have used this paradigm since the earliest review (Holmes & Bourne, 2008) until July 2014. Highlighting the different stages of trauma processing, i.e. pre-, peri- and post- trauma, the studies are divided according to manipulations before, during and after film viewing, for experimental as well as correlational designs. While the majority of studies focussed on the frequency of intrusive memories, other reactions to trauma were also modelled. We discuss the strengths and weaknesses of the trauma film paradigm as an experimental psychopathology model of trauma, consider ethical issues, and suggest future directions. By understanding the basic mechanisms underlying trauma symptom development, we can begin to translate findings from the laboratory to the clinic, test innovative science-driven interventions, and in the future reduce the debilitating effects of psychopathology following stressful and/or traumatic events. Highlights: After trauma symptoms of post-traumatic stress such as intrusive memories may develop The trauma film paradigm offers an experimental psychopathology model to study trauma We reviewed 74 articles that used the paradigm since the earliest review in 2008 The paradigm can guide clinical innovation, such as targeting intrusive memories DSM-5'sPTSD Criteria A allows for trauma exposure through work related movie viewing